The assembly of (+)‐vincadifformine‐ and (−)‐tabersonine‐derived monoterpenoid indole alkaloids in Catharanthus roseus involves separate branch pathways. (21st May 2019) - Williams, Danielle; Qu, Yang; Simionescu, Razvan; De Luca, Vincenzo
Summary: The biological activity of monoterpenoid indole alkaloids (MIAs) has led to their use in cancer treatment and other medical applications. Their biosynthesis has involved the formation of reactive intermediates by responsible enzymes to elaborate several different chemical scaffolds. Modification of scaffolds through different substitution reactions has produced chemically diverse MIAs and related biological activities. The present study characterizes the three‐step pathway involved in the formation of (+)‐echitovenine, the major O ‐acetylated MIA of Catharanthus roseus roots, and differentiates it from a parallel pathway involved in the formation of hörhammericine. Separate hydrolases convert a common reactive MIA intermediate to aspidosperma skeletons of opposite specific rotations, that is (+)‐vincadifformine and (−)‐tabersonine, respectively. The formation of (+) minovincinine from (+) vincadifformine 19‐hydroxylase (V19H) is catalyzed by a root‐specific cytochrome P450 with high amino acid sequence similarity to the leaf‐specific tabersonine‐3‐hydroxylase involved in vindoline biosynthesis. Similarly, O ‐acetylation of (+)‐minovincinine to form (+) echitovenine involves minovincinine‐ O ‐acetytransferase. The substrate specificity of V19H and MAT for their respective (+)‐enantiomers defines the separate enantiomer‐specific pathway involved in (+)‐echitovenine biosynthesis and differentiates it from a parallel (−)‐enantiomer‐specific pathway involved in the formation of hörhammericine from (−)‐tabersonine. Significance Statement: Separate enantiomer‐specific branch pathways are responsible for the formation of hörhammericine and (+)‐echitovinine, the two major aspidosperma monoterpenoid indole alkaloids belonging to opposite optical series found in Catharanthus roseus roots. Our results elucidate the three‐step pathway involved in the formation of the (+)‐enantiomer of echitovenine and differentiate it from a recently described parallel pathway responsible for the biosynthesis of hörhammericine.